2002
DOI: 10.1016/s0304-3959(01)00427-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender, coping and the perception of pain

Abstract: Research consistently indicates that gender differences exist in pain perception, with females typically reporting more negative responses to pain than males. It also seems as if males and females use and benefit from different coping strategies when under stress; females seem to prefer emotion-focused coping, whereas males prefer sensory-focused coping. Unfortunately, experimental research that examines such differences in the context of pain has not yet been adequately investigated. The aim of the current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
149
8
13

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(180 citation statements)
references
References 27 publications
10
149
8
13
Order By: Relevance
“…One study by Keogh and Herdenfeldt (2002) showed that pain coping instructions had different effects on the pain experience of males and females.…”
Section: Gendermentioning
confidence: 99%
“…One study by Keogh and Herdenfeldt (2002) showed that pain coping instructions had different effects on the pain experience of males and females.…”
Section: Gendermentioning
confidence: 99%
“…The effect of self-perceived role identity on pain perception, here defined as the product of the brain's abstraction and elaboration of a nociceptive input (Basbaum and Jessell, 2000), has been investigated in gender role studies, including coping strategies (Keogh and Herdenfeldt, 2002), pain catastrophizing (Thorn et al, 2004), situational context (Kallai et al, 2004), gender role expectations (Robinson et al, 2001) and hyper-vigilance (Rollman et al, 2004) or anxiety (Edwards et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The obtained data with popular and lyrical singers do not corroborate the data obtained to general population (4) , which the mean of pain in women is higher than men, suggesting that singing itself may reduce the amount of reported pain in general to both genders. Other studies about pain point out men and women are different regarding pain coping, threshold, and tolerance, women had higher complaints and lower resistance (13)(14)(15) . Regarding predominant pains, the three most reported pains by popular singers were all proximal to larynx: sore throat (66%), pain to speak (41%), and neck pain (35%).…”
Section: Discussionmentioning
confidence: 95%
“…These data suggest proximal pain to larynx complaint are more resident in people reporting vocal problems and then pain next to the larynx region during the practice of singing might indicate the presence or predisposition to the urge of voice disturbances, and restricting singing activity. The presence of small voice deviation in a singer may bring big financial impact, shows and presentations canceled and restricting the professional exercise (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) . In the studied sample there was a big search for otolaryngologists and speech language pathologists due to vocal disturbances and a correlation between the searches with the presence of body pains (Table 4).…”
Section: Discussionmentioning
confidence: 99%